Investment Policy and Promotion Diagnostics and Tools : Maximizing the Potential Benefits of Foreign Direct Investment for Competitiveness and Development - World Bank Group (World Bank, Washington, DC, 2017)
This paper presents a bird’s eye overview of the investment policy and promotion (IPP) logical framework developed by the trade and competitiveness global practice of the WBG to address the challenge of how countries can use foreign direct investment (FDI) to advance their economic development. The report sets out three key propositions: i.e. (i) that investment policy should aim not to choose between but connect domestic and foreign investors, (ii) that investment policy making should be based on the whole investment cycle going beyond promotion and (iii) that not all FDI is the same nor has the same development impacts. This sets out the logical framework for a concrete investment policy and promotion intervention in a time of globalization that will yield measurable results.